Exploring the evidence behind the comparable impact of the pneumococcal conjugate vaccines PHiD-CV and PCV13 on overall pneumococcal disease - Patricia Izurieta; Javier Nieto Guevara (Taylor & Francis Group, 2022)
The worldwide implementation of pneumococcal conjugate vaccines (PCVs) in children has reduced the overall pneumococcal disease burden. Two PCVs are widely available for infant vaccination: the pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) and the 13-valent PCV (PCV13). While these PCVs differ in serotype composition (PCV13 includes polysaccharides of serotypes 3, 6A and 19A; PHiD-CV does not), their impact on the overall pneumococcal disease burden in children is comparable. This commentary summarizes the evidence of comparability between PHiD-CV and PCV13 and explores why differences in serotype composition may not necessarily translate into a differential clinical impact. Both vaccines confer similarly high protection against disease caused by vaccine serotypes and lead to a partial replacement by non-vaccine serotypes. PHiD-CV does not protect against serotype 3 disease (not included in the vaccine) and PCV13's effect on this serotype has been inconsistent. PHiD-CV provides some cross-protection against disease caused by vaccine-related serotype 19A but neither vaccine has fully controlled 19A disease. While protection against 19A is higher for PCV13 than PHiD-CV, replacement by non-PCV13 serotypes in settings with a PCV13 program appears to compensate for this difference. This results in a similar residual overall disease burden with both vaccines.